KAJIAN LITERATUR TENTANG KONSEP TAWAKAL SERTA RELEVANSINYA DALAM KEHIDUPAN SOSIAL - Tammar, Ardiansyah; Abubakar, Achmad; Mahfudz, Muhsin (Farabi, 2023)
This article aims to conduct a literature review analysis of the concept of "tawakal," with the intention of summarizing, understanding, and comprehensively exploring the definitions, dimensions, as well as religious aspects that appear in various existing literature. The research method used is the Systematic Literature Review (SLR) with the goal of identifying, evaluating, and examining all relevant studies to provide answers to the research questions that have been established. Article searches were conducted using the keyword "tawakal concept" within the time frame from 2018 to 2023. Literature selection was based on inclusion criteria, which encompassed studies directly related to the concept of tawakal and studies whose research findings have been published in national journals or proceedings. The results of the selection showed that there were 8 articles relevant to the keyword. In conclusion, tawakal is an important concept in Islam that teaches complete dependence on Allah while making the best possible effort. Tawakal brings many benefits, including inner peace, strengthening of faith, a life free from excessive worries, an improved relationship with Allah, instilling hope, the development of Islamic character, and a positive outlook on life. In daily life, tawakal helps individuals lead their lives with full trust in Allah and the belief that He is a faithful Helper.